Conducting teachers to refer students with school complaints to the health system: scope review protocol (Research, Society and Development, 2022)
School complaints are requests made by teachers, coordinators, parents or guardians, referring to difficulties and problems identified in students at school. The flow of students referred to the health system has been increasing daily. This protocol aims to map the literature on school complaints and student flows to the Health System. The protocol was developed according to the recommendations of the Joanna Briggs Institute Manual and registered in the Open Science Framework. The following databases will be used: Latin American and Caribbean Literature on Health Sciences (LILACS), Medical Literature Analysis and Retrieval Sistem on-line (Medline) and Scientific Electronic Library On-line (SciELO), the gray literature search will be carried out through Google Scholar. The data will be obtained and presented in the form of tables, images and/or tables in a descriptive way, as indicated in the checklist proposed by PRISMA-ScR. This protocol will make it possible to carry out a scope review, with a rigorous and transparent methodology, based on it, to obtain greater knowledge about the conduct of teachers to refer students with school complaints to the health system.